SAT0155 Signature of Inflammatory Genes in B-Cells and Double Negative Memory Phenotype as Biomarkers of Response To Tocilizumab. (15th July 2016) - Fedele, A.L.; Tolusso, B.; Canestri, S.; Gremese, E.; Di Mario, C.; Di Sante, G.; Alivernini, S.; Ferraccioli, G.
Abstract : Background: Tocilizumab (TCZ) is an effective treatment in Rheumatoid Arthritis (RA) inducing modifications of B cell subsets in vivo. 1–3 Objectives: To define whether the study of circulating B cell subsets could represent a possible tool to understand the pharmacological action of TCZ, helping the clinician to identify the best responders to IL6R blockade. Methods: 70 RA patients (age 52.3±15.2 years, disease duration 8.5±10.1 years, 74.3% female) not responder to previous cDMARDs (n=39) and/or bDMARDS (n=31) were enrolled in the study, of which 19 (27.1%) with early RA (ERA) and 51 (72.9%) with a long-standing disease (LSRA). All patients were treated with TCZ at a dose of 8 mg/kg every 4 weeks. At each visit remission was evaluated according to ACR/EULAR criteria 4 and peripheral blood (PB) derived B cells were collected for the analysis of B-cell subsets distribution by FACS using IgD-CD27 classification 5 . Among them, PB-derived B cells from 13 bDMARDs naïve RA patients were analyzed for specific genes expression through RT-PCR. Results: In RA cohort, 16.7% and 19.3% of TCZ-treated RA patients reached ACR/EULAR remission (SDAI≤3.3) at 6th and 12th months FU. At TCZ baseline, a higher percentage of post-switched memory B-cells (p=0.005) together with plasmablasts (p<0.001) and a lower percentage of pre-switched memory B cells (p=0.01) were observed in RA patients compared to Healthy Controls (HC, n=45) mainly in bDMARDs naïve patients. After TCZ treatment, we showed an increase of pre-switched memory and a reduction of post-switched memory and double negative (DN) B cells in responders, more evident in patients reaching remission. In particular, patients reaching SDAI remission at 6 and 12 months of TCZ-treatment had a higher reduction of DN B cell subsets already after 3 months reaching a comparable value as in HC ( p <0.05). At the multivariate analysis, a disease duration less than 12 months [OR (95%CI): 18.0 (1.6–203.9)], a moderate disease activity (SDAI≤26) at baseline [OR (95%CI): 20 (1.7–250)] and a higher reduction of DN B cells at 3 months of FU [OR (95%CI): 1.05 (1.01–1.08)] arose as significant independent predictors of ACR/EULAR remission (SDAI≤3.3) at 6th months of TCZ treatment. Finally, TCZ-treatment seems to influence B-cell genes expression inducing an up-regulation of proinflammatory molecules (TNF-alpha, IL6) genes, together with the related STAT3, SYK and ZAP-70 genes, in the earlier treatment phases (3 and 6 months respectively) and the subsequent down-regulation of their receptors (TNF-RII and IL6R). Interestingly, the expression of JAK1 decreased significantly at the 12th month, whereas that of JAK3 did not change at the different time points. Conclusions: In our cohort of TCZ-treated RA patients, a significant reduction of DN memory B cells at the 3th month of FU has emerged as an early biomarker of remission afterwards. At the same time, profound effects at the JAK1 gene level occurred in B cells after TCZ treatment, even if an increase of Syk and ZAP-70 genes expression was observed, suggesting that B cells are not fully deactivated even after 6–12 months of treatment. References: Roll P et al. Arthritis Rheum 2011; Muhammad K et al. Ann Rheum Dis 2011; Mahmood Z et al. Arth Res Ther 2015; Felson DT et al. Arthritis Rheum 2011; Sanz I et al. Semin Immunol 2008. Disclosure of Interest: None declared